IT Affordances, Flow, and Perceived Scarcity: A Study on Impulsive Buying Behavior and Post-Purchase Dissonance in Live Shopping - Simanjuntak, Evi Rinawati; Pratama, Rendy Setya (Bina Nusantara University, 2024)
Live shopping has evolved significantly as extensive publications have explored this phenomenon from the perspective of streamers and consumers. However, there is limited analysis from the human-computer interaction perspective, particularly concerning IT affordances. Therefore, the research aimed to enhance the understanding of human-computer interaction in live streaming sessions, exploring flow experiences and the influence on impulsive buying behavior, which led to postpurchase dissonance. The moderating role of perceived scarcity was also examined. The research adopted convenience sampling and obtained 250 online survey responses. The data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) to test the hypotheses. The results show that three IT affordance components, visibility, metavoicing, and interactivity, foster flow experiences, but guidance shopping does not. Furthermore, flow experiences are found to stimulate impulsive buying behavior, which subsequently leads to post-purchase dissonance. The results further show a negative impact of perceived scarcity on buying behavior, while the effect of scarcity is anticipated to enhance buying motivation. These results contribute to understanding the significant drivers of flow experiences in live shopping and the implications of perceived scarcity. Enhancing interactive communication between streamers and viewers is essential for businesses while promoting attractive visibility and comprehensive product information during live shopping sessions. Additionally, scarcity effects should be approached with caution only when necessary to accelerate the call to action.